Effects of the precipitation pH on the ethanolic precipitation of sugar beet pectins. (January 2016) - Guo, Xiaoming; Meng, Hecheng; Tang, Qiang; Pan, Runquan; Zhu, Siming; Yu, Shujuan
Abstract: Sugar beet pectins (SBP) were precipitated from a purified extract in a 75% v/v ethanol solution at an initial extract pH (I-pH) ranging from 2.0 to 4.5. The effects of I-pH on pectin yield and pectin-cation interactions were studied. No simple correlation between pectin yield and I-pH was observed. The lowest pectin yield was obtained by precipitating the acidic pectin extract with ethanol at I-pH 4.5. Pectin yield increased to a maximum value as I-pH decreased from 4.5 to 3.0. These results indicated that decreased electrostatic repulsion between pectin chain segments enhanced pectin chain–chain interactions, thereby improving the precipitation effect. A decrease in pectin yield was observed as I-pH decreased below 3.0. The cation content of various samples was measured by high-performance cation-exchange chromatography in order to determine the content of SBP-bound cations during precipitation. Cation content and degree of cation binding were measured for pectins precipitated at I-pH 3.0, 2.5, and 2.0, and the results revealed that a decrease in pectin yield accompanied a decrease in cation–pectin interactions. These results suggest that the precipitation of SBP from an aqueous extract involves complex interactions between cations, solvent molecules, and pectin chain segments. The larger precipitation effect observed with divalent ions compared to monovalent ions may be due to enhanced inter-chain interactions between pectin molecules, probably via the formation of intermolecular bonds. Graphical abstract: Highlights: Solubility of pectins in the ethanolic solution depended on the pH at which pectins were precipitated. No simple correlation between precipitation pH and pectin yield was observed. Effects of precipitation pH on the pectin-cation interactions were investigated. Interactions between charged pectins and divalent cations promoted the precipitation of pectins.